Каменное зодчество Древней Руси - Бусева-Давыдова Ирина Леонидовна (Библиотечная серия, 1989)
Экземпляры: (20200703) / Инвентарный номер: 18657 / Цена: / Сис.шифр: 85.113(2Р=Рус) / Авт.знак: Б92 / ГРНТИ: 67.07.29 / ББК: 85.11